As aulas de música enquanto espaço de formação crítica e identitária: da localização social dos sujeitos às pedagogias que fazem sentido no chão da escola - Bezerra, Maria das Dores (2018)
This research investigated the musical preferences of the students of a municipal school in Juazeiro do Norte-CE, starting from their daily experiences, social location and identifications. Recognizing the impossibility of ignoring the mass access of students to the artistic works propagated by the Cultural Industry (ADORNO & HORKHEIMER, 1947), we defend the innovation of music teaching in school based on musical appreciation, dialogue and critical formation of students, in order to favor a critical stance on mass culture. To deny the influence of this access in the daily life does not corroborate with the dialogue (BOHM, 1998) between school, experience (BONDIA, 2002; BENJAMIN, 1987) and sense (DUARTE Jr., 2000). The methodologies adopted were qualitative, allowing the evidence of the information in the light of the investigated subjects (MINAYO, GOMES and DESLANDES, 2009), and the action research, since it enables the researcher to analyze the data collected and their role as participants in the investigative process (BRANDÃO, 1987). Realizing that Cultural Industry hits did not represent student music was one of the main findings of this research. In defending their identifications (HALL, 2004, 2005) and social location, the students criticized the mass media and the marginalization of their music, listing and positioning RAP at the top of their preferences. This analysis pointed to the construction of a methodology that made sense on the floor of the school, which approached school and student, considering their daily lives and reverberating in a pedagogical fluency for teaching music in school.